2001
DOI: 10.1054/bjoc.2001.2026
|View full text |Cite
|
Sign up to set email alerts
|

PDEPT: polymer-directed enzyme prodrug therapy

Abstract: Summary Polymer-directed enzyme prodrug therapy (PDEPT) is a novel two-step antitumour approach using a combination of a polymeric prodrug and polymer-enzyme conjugate to generate cytotoxic drug selectively at the tumour site. In this study the polymeric prodrug N-(2-hydroxypropyl) methacrylamide (HPMA) copolymer-Gly-Phe-Leu-Gly-doxorubicin conjugate PK1 (currently under Phase II clinical evaluation) was selected as the model prodrug, and HPMA copolymer-cathepsin B as a model for the activating enzyme conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For example, retrospective analysis of clinical data from PPX Phase III trials in advanced lung cancer patients [36] showed improved survival in female but not in male patients, and it has been postulated that patient oestradiol level might play a pivotal role as oestrogens are known to induce cathepsin B activity. Earlier studies involving FCE28068 in s.c. B16F10 tumours [15, 37] indicated an ~30 min time lag before Dox release began, supporting the hypothesis of drug release following endocytic internalisation [38]. However, it should be noted that other factors may play a role in controlling the rate of drug release: (i) rate of conjugate diffusion through the tumour interstitium [39], (ii) the rate of endocytic internalisation (endocytic gateways and intracellular trafficking pathways are often dysregulated in cancer [40]) and (iii) exposure to cathepsin B in the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…For example, retrospective analysis of clinical data from PPX Phase III trials in advanced lung cancer patients [36] showed improved survival in female but not in male patients, and it has been postulated that patient oestradiol level might play a pivotal role as oestrogens are known to induce cathepsin B activity. Earlier studies involving FCE28068 in s.c. B16F10 tumours [15, 37] indicated an ~30 min time lag before Dox release began, supporting the hypothesis of drug release following endocytic internalisation [38]. However, it should be noted that other factors may play a role in controlling the rate of drug release: (i) rate of conjugate diffusion through the tumour interstitium [39], (ii) the rate of endocytic internalisation (endocytic gateways and intracellular trafficking pathways are often dysregulated in cancer [40]) and (iii) exposure to cathepsin B in the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Several drug conjugates have also been synthesized with enzyme-cleavable substrates. In one of the earliest manifestations of this technique, Duncan and his coworkers conjugated antitumor drugs to N-(2-hydroxypropyl)methacrylamide (HPMA) using cathepsin B-degradable peptide linkages [ 242 , 539 ]. The prodrug structure released the payload in several hours.…”
Section: Stimulimentioning
confidence: 99%
“…6 Another way to avoid immunogenicity is polymer-directed enzyme-prodrug therapy (PDEPT). 7 In this approach a polymer-drug conjugate is injected first and accumulates in the tumor tissue by a mechanism called enhanced permeability and retention effect (EPR). 8 Afterward an enzyme-polymer conjugate is injected that activates the prodrug at the tumor site.…”
mentioning
confidence: 99%